FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN GIZI LEBIH PADA SISWA TAMAN KANAK-KANAK DI KECAMATAN DENPASAR BARAT - Dharmadi, I Gde Made Swastika; Utami, Ni Wayan Arya (ARCHIVE OF COMMUNITY HEALTH; Vol 5 No 1 (2018): Juni (2018)DO - 10.24843/ACH.2018.v05.i01.p10, 2020)
ABSTRACT Overweight case is one of nutritional problems toward society for all ages especially society in developed country. According to several researches, increasing numbers of overnutrient case tend to be experienced by preschool children and they risk becoming overweight and obese adults. Prevalence of overweight children ages 3-6 years old which is more increasing year by year. The aim of this research is to know the representation and the factors which relate with overweight preschool children case. This research used cross-sectional analysis with 75 children as sample size who are students in west Denpasar Kindergarten; which are took in cluster sampling for determining kindergarten sample and simple random sampling for determining kindergarten sample size. The data is collected by interview method and is analysed in univariate and bivariate. The result showed that representation of overweight kindergarten children case in west Denpasar kindergarten is 20%. Value factors which influence the overweight kindergarten children case were fast food consumption (PR=2,98; p<0,0131), light physical activities (PR= 4,17, P=0,0008), exclusive breastfeeding (PR=0.34; p=0,0184), mother’s nutritional status (PR=4,61; p=0,0013), , mother’s working status (PR=2,68; p=0,0356). Collaboration of parents, school participation, and banjar environment are needed in prevention of overweight so that they can play active role in preventing children since early stage. Furthermore, if the researcher wants to do similar with this research, is expected could be better in measuring physical activities and respondents’ nutrient intake. Keywords : Overweight, Kindergarten, Exclusive Breastfeeding, Mother’s Nutritional Status, Fast Food Consumption